A process strategy planning of additive-subtractive hybrid manufacturing based multi-dimensional manufacturability evaluation of geometry feature. (April 2023) - He, Yu; Wei, Jiacheng; He, Yuyu; Rong, Xiaoxu; Guo, Wenfeng; Wang, Fei; Wang, Yang; Liu, Junyan
Abstract: Additive-subtractive hybrid manufacturing (ASHM) combines the advantages of both additive manufacturing (AM) and subtractive manufacturing (SM), which plays an important role in high efficiency, quality, precision production of complex structural parts. However, it is significant that an effective process planning strategy is developed to choose the correct fabrication technique for a given part manufacturing. It is reported on a novel process planning approach of ASHM that is employed for the geometrical structure decomposition of complex part, decision-making of AM, SM and their alternation based on multi-dimensional manufacturability evaluation. The proposed approach is able to optimize manufacturing resources, time and cost and minimize complex geometric structure fabrication by considering the full advantages of AM and SM. A series of manufacturing constraint rules are proposed to screen the alternative manufacturing schemes which refer to process selection for features between AM and SM. Four manufacturability indexes, including material utilization, manufacturing cost, manufacturing time and local machining complexity, are established and used for the quantitative manufacturability evaluation of structure fabricated by AM, SM as well as ASHM. A decision support criterion termed as "Comprehensive Hybrid Manufacturing Complexity Index (CHCI)" has been developed, this comprehensively took into account the influence of each index and its relative importance on manufacturability. Furthermore, CHCI values are calculated using the digraph and matrix method, and they are applied to confirm the optimal manufacturing scheme from a set of possible manufacturing schemes. Finally, three experimental numerical case studies were performed to demonstrate the efficacy of the proposed method. Highlights: Four manufacturability indexes are established and used for the quantitative manufacturability evaluation of structure fabricated by additive-subtractive hybrid manufacturing (ASHM). A decision support criterion termed as "Comprehensive Hybrid Manufacturability Complex index (CHCI) has been developed. The proposed process strategy planning method can confirm the optimal ASHM scheme based on multi-dimensional manufacturability evaluation.